THE REPRESENTATION OF MADURESE ISLAM ON YOUTUBE: SEMIOTICS ANALYSIS ON THE COMEDY SHOW 'DHE'REMMAH CONG' - Aditya Fahmi Nurwahid; Citra Safira (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Madurese Islam is one of the cultural treasures of Islam in Indonesia. Madurese culture is intimately intertwined with Islam and reflects diverse perspectives on matters of politics, society, culture, and economics. The emergence of new media has resulted in the digitalization of Madurese Islam, exemplified by its presence on the Tretan Universe YouTube channel. The objective of this study is to provide a semiotic analysis of the Madurese Islamic da'wah content portrayed in the satirical comedy show